2016
DOI: 10.1111/febs.13816
|View full text |Cite
|
Sign up to set email alerts
|

Blocking glutamate carboxypeptidase II inhibits glutamate excitotoxicity and regulates immune responses in experimental autoimmune encephalomyelitis

Abstract: Experimental autoimmune encephalomyelitis (EAE) is an inflammatory disease in the murine central nervous system (CNS) and recapitulates the clinical and pathological features of human multiple sclerosis (MS). Glutamate carboxipeptidase II (GCPII), an enzyme expressed exclusively on astrocytes, is known to affect the disease progression of various neurological disorders by producing glutamate. Despite several findings indicating possible link between glutamate and MS/EAE, however, the involvement of astrocyte o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 40 publications
(60 reference statements)
2
25
0
Order By: Relevance
“…In EAE, aberrations in the expression of Glu transporters, receptors or metabolizing enzymes were detected which suggested the role of excitotoxicity in this model of MS. Pathological changes like axonal damage, demyelination, and ODC loss were observed which are exhibitive of excitotoxicity. The use of GluR antagonists could suspend these effects and cause disease amelioration [6,27,28,29,30,31]. …”
Section: Excitotoxicity In Multiple Sclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…In EAE, aberrations in the expression of Glu transporters, receptors or metabolizing enzymes were detected which suggested the role of excitotoxicity in this model of MS. Pathological changes like axonal damage, demyelination, and ODC loss were observed which are exhibitive of excitotoxicity. The use of GluR antagonists could suspend these effects and cause disease amelioration [6,27,28,29,30,31]. …”
Section: Excitotoxicity In Multiple Sclerosismentioning
confidence: 99%
“…Ha et al (2016) [29] examined the impact of an efficient GCPII inhibitor, 2-phosphonomethyl pentanedioic acid (2-PMPA), on EAE mice and detected improvement in disease course and significantly decreased amounts of inflammatory cells infiltrating the CNS. This agent impeded the expression of mGluR1 in CNS and periphery too.…”
Section: Therapeutic Trialsmentioning
confidence: 99%
“…1 As a major regulator of extracellular glutamate availability in the brain, 2 GCPII inhibition represents a promising drug target for multiple diseases associated with disrupted glutamate homeostasis including neuropathic pain, 37 stroke, 2 diabetic neuropathy, 810 schizophrenia, 11 addiction, 1214 multiple sclerosis, 1517 and traumatic brain injury. 18,19 Selective inhibitors of GCPII have been shown to attenuate glutamate-mediated excitotoxicity, and ameliorate these disease phenotypes in preclinical models.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that increased glutamate levels are responsible for increased production of inflammatory cytokines in activated T cells in autoimmune diseases [41]. 2-PMPA treatment dampened the function of CD4 + T cells (such as T H 1 and T H 17), suppressed mGluR1 expression in both periphery and CNS, and reduced the number of mGluR1-positive CD4 + T cells in experimental autoimmune encephalomyelitis [42]. It has been reported that NAAG receptors can be found in the GI tract, though the roles of NAAG or glutamate in the GI tract are not well characterized [43].…”
Section: Discussionmentioning
confidence: 99%